2008
DOI: 10.1002/ajmg.b.30663
|View full text |Cite
|
Sign up to set email alerts
|

Variation in GABA‐A subunit gene copy number in an autistic patient with mosaic 4 p duplication (p12p16)

Abstract: Autism has been associated with chromosomal aberrations, including duplications at chromosome 4, and the identification of genetic factors contributing to the etiology of this disease is the focus of much research. Here we report a Japanese girl with mosaic of chromosome 4p duplication, mos 46,XX,dup(4)(p12p16)[54]/46,XX[6], who was diagnosed with autism at 3 years of age. Fluorescence in situ hybridization (FISH) with probes covering the region spanning a cluster of the gamma aminobutyric acid A (GABA-A) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…Maybe it has also to be considered that the mosaicism present in the reported case could also be responsible for the lack of symptoms, as it has recently been shown that different body tissues can vary significantly in mosaic-expression of sSMC carriers [Fickelscher et al, 2007]. Overall, apart from the case reported here, there is no comparable case in the literature with such a small imbalance in 4p; there is only a larger one which includes 4p16 to 4p12 reported by Kakinuma et al [2008]. Thus, we have to wait for further reports on duplications to clarify the question if proximal 4q may harbor a UBCA.…”
contrasting
confidence: 45%
“…Maybe it has also to be considered that the mosaicism present in the reported case could also be responsible for the lack of symptoms, as it has recently been shown that different body tissues can vary significantly in mosaic-expression of sSMC carriers [Fickelscher et al, 2007]. Overall, apart from the case reported here, there is no comparable case in the literature with such a small imbalance in 4p; there is only a larger one which includes 4p16 to 4p12 reported by Kakinuma et al [2008]. Thus, we have to wait for further reports on duplications to clarify the question if proximal 4q may harbor a UBCA.…”
contrasting
confidence: 45%
“…CNV may also act as a susceptibility factor as has been described at the 7q11.23 segmental duplications for the Williams-Beuren syndrome deletion (30, 70). Microdeletions and microduplications in genes have been associated with autism (30, 108,116,186,237,384).…”
Section: Aneuploidy Syndromes and Phenotypic Variabilitymentioning
confidence: 99%
“…This chromosomal abnormality was found to be a de novo alteration because both her parents were healthy and have normal chromosomes. 5 Another case report describes two brothers, 12 and 11-years-old, with autism and a maternally inherited paracentric inversion of a short arm of chromosome 4 [46,XY,inv(4)(p12p15.3)mat] disrupting the GABRG1 receptor gene, which was inherited from their mother. 6 Last, there is one case report of an 18-year-old female with autistic disorder, intellectual disability and a duplication of 4p13 to 4p12 [46,XX,dup(4)(p12p13)].…”
Section: Discussionmentioning
confidence: 99%